(untitled) (Journal Of Educational and Psychological Researches, 2023)
The current research aims to identify the effect of the program to develop the skill of friendship among kindergarten children, as well as the scope of the impact of the program on the sample. To achieve the objectives of the research, the researcher hypothesizes there is no significant difference between the average scores of the sample members on the friendship skill scale for the dimensional scale according to the experimental and control group. The research sample consisted of (60) girl and boy with age ranges (4-6) who were randomly selected from the Kindergarten Unity at Baghdad city/ Rusafa 1. The children were distributed into an experimental and control group, each group consists of (30) girl and boy. The two groups were chosen randomly. To achieve the objectives of the research, the researcher developed a scale of friendship skills for kindergarten children and a training program. The researcher used the experimental design with partial control for the experimental and control groups of the pre-posttest. The results showed that there is a statistically significant difference between the average scores of the children of the experimental group and the control group on the scale of friendship skill in the post-test. The independent variable of the training program has an effect on the variable of the skill of friendship. The research came out with a set of recommendations and suggestions.